2009
DOI: 10.1590/s0103-84782009000300014
|View full text |Cite
|
Sign up to set email alerts
|

Reguladores vegetais e atividade de invertases em cana-de-açúcar em meio de safra

Abstract: RESUMO O objetivo neste trabalho foi a avaliação da atividade das invertases ácida e neutra e a função que essas exercem no controle do acúmulo de sacarose em cana-de-açúcar, variedade SP80-3280, decorrente da aplicação de reguladores vegetais no meio de safra, em Igaraçu do Tietê (SP).Reguladores vegetais e atividade de invertases em cana-de-açúcar em meio de safra Growth regulators and activity invertases in the middle of the cropping season Recebido para publicação 27.12.07 Aprovado em 26.11.08

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
14

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 15 publications
1
14
0
14
Order By: Relevance
“…Constatou-se ainda que a maioria das variáveis que apresentaram resposta significativa apresentou redução quando as sementes foram tratadas com doses muito elevadas (20 mL kg -1 de sementes), indicando que quantidades excessivas de bioestimulante podem provocar efeito tóxico à planta e baixo aproveitamento dos hormônios vegetais, podendo assim resultar em perda na eficiência agronômica do biorreguladores (LEITE et al, 2009), a eficiência agronômica dos biorreguladores é afetada de forma significativa pela dosagem, uma vez que quantidades excessivas podem provocar efeito tóxico à planta e baixo aproveitamento dos hormônios vegetais. …”
Section: Resultsunclassified
“…Constatou-se ainda que a maioria das variáveis que apresentaram resposta significativa apresentou redução quando as sementes foram tratadas com doses muito elevadas (20 mL kg -1 de sementes), indicando que quantidades excessivas de bioestimulante podem provocar efeito tóxico à planta e baixo aproveitamento dos hormônios vegetais, podendo assim resultar em perda na eficiência agronômica do biorreguladores (LEITE et al, 2009), a eficiência agronômica dos biorreguladores é afetada de forma significativa pela dosagem, uma vez que quantidades excessivas podem provocar efeito tóxico à planta e baixo aproveitamento dos hormônios vegetais. …”
Section: Resultsunclassified
“…+ Glyphosate, and Sulfomethuron-methyl ( Figure 2E). LEITE et al (2009) reported high correlation between the invertases activity and the weather conditions at the middle of the season where the acid activity was higher in weather conditions favorable to plant vegetative development and when the weather conditions were favorable to natural ripening the neutral invertases activity increased.…”
Section: Resultsmentioning
confidence: 98%
“…The highest activity of SPS and the lowest activity of SAI probably resulted in an increase in the concentration of sucrose in the winter, at low temperatures, suggesting that the activity of SPS is one of the factors involved in the control of sucrose accumulation in sugarcane. Leite et al (2009) observed an increase in SAI activity through the use of chemical ripeners under high precipitation, a condition favorable for sugarcane plant development. However, when subjected to decreases in temperature and precipitation, which are favorable conditions for natural ripening, the application of chemical ripeners resulted in elevated NI activity.…”
Section: The Role Of Enzymes In Ripeningmentioning
confidence: 95%
“…Plant growth regulators promote distinct and significant alterations in the enzymatic activities of acid and neutral invertases (Leite et al, 2009, Siqueira, 2009). …”
Section: The Role Of Enzymes In Ripeningmentioning
confidence: 99%
See 1 more Smart Citation